1985
DOI: 10.1097/00006842-198507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic stress and glycemic control: a comparison of patients with and without proliferative diabetic retinopathy.

Abstract: Using a case/control design, patients with (cases) and without (controls) proliferative diabetic retinopathy were compared using three psychosocial measures: life events, psychiatric symptomatology, and ego development. Cases reported significantly more symptoms. They also demonstrated a modest and significant correlation of negative life events with HgbA1c that was not shown in the controls. When the relationship of life events with glycemic control was explored in cases of varying durations of proliferative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Despite receiving oral medication and psychotherapy for depression, these subjects indicated that their depressive symptoms were exacerbated after the onset of T1DM. [34][35][36][37][38] We thank Dr. E. O'Brian Smith for his help with the statistical analysis of the data. We also thank the faculty, Nurse Practitioners, Certified Diabetes Educators, Registered Nurses, and auxiliary staff of the Diabetes Clinic for help in recruiting subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite receiving oral medication and psychotherapy for depression, these subjects indicated that their depressive symptoms were exacerbated after the onset of T1DM. [34][35][36][37][38] We thank Dr. E. O'Brian Smith for his help with the statistical analysis of the data. We also thank the faculty, Nurse Practitioners, Certified Diabetes Educators, Registered Nurses, and auxiliary staff of the Diabetes Clinic for help in recruiting subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies provide additional supporting evidence. Jacobson et al [1985] found that proliferative diabetic retinopathy heralded the onset of depression in patients with type 1 diabetes. Miyaoka et al [1997] also reported an association between retinopathy and mood symptoms in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…First, poor mental health attributed to lack of work control can also contribute to the development and/or progression of a wide range of common medical conditions such as joint pains, pruritus, psorasis, and urticaria (Carney & Freedland, 2000). In particular, depression has been associated with diabetes and poorer metabolic control (Garvard, Lustman, & Clouse, 1993;Jaconson, Rand, & Hauser, 1985). Second, lack of control at work imposes structural constraints on choices regarding healthrelated behaviors and may result in an unhealthy lifestyle (Wickrama et al, 1995).…”
Section: Previous Studiesmentioning
confidence: 99%